A PAS domain-containing regulator controls flagella-flagella interactions in Campylobacter jejuni - Reuter, Mark; Periago, Paula M.; Mulholland, Francis; Brown, Helen L.; Van Vliet, Arnoud H. (Frontiers in Microbiology, 2015)
The bipolar flagella of the foodborne bacterial pathogen Campylobacter jejuni confer motility, which is essential for virulence. The flagella of C. jejuni are posttranslationally modified, but how this process is controlled is not well understood. In this work, we have identified a novel PAS-domain containing regulatory system, which modulates flagella-flagella interactions in C. jejuni. Inactivation of the cj1387c gene, encoding a YheO-like PAS6 domain linked to a helix-turn-helix domain, resulted in the generation of a tightly associated 'cell-train' morphotype, where up to four cells were connected by their flagella. The morphotype was fully motile, resistant to vortexing, accompanied by increased autoagglutination, and was not observed in aflagellated cells. The Δcj1387c mutant displayed increased expression of the adjacent Cj1388 protein, which comprises of a single endoribonuclease L-PSP domain. Comparative genomics showed that cj1387c (yheO) orthologs in bacterial genomes are commonly linked to an adjacent cj1388 ortholog, with some bacteria, including C. jejuni, containing another cj1388-like gene (cj0327). Inactivation of the cj1388 and cj0327 genes resulted in decreased autoagglutination in Tween-20-supplemented media. The Δcj1388 and Δcj0327 mutants were also attenuated in a Galleria larvae-based infection model. Finally, substituting the sole cysteine in Cj1388 for serine prevented Cj1388 dimerisation in non-reducing conditions, and resulted in decreased autoagglutination in the presence of Tween-20. We hypothesize that Cj1388 and Cj0327 modulate posttranslational modification of the flagella through yet unidentified mechanisms, and propose naming Cj1387 the Campylobacter Flagella Interaction Regulator CfiR, and the Cj1388 and Cj0327 protein as CfiP and CfiQ, respectively.